Study protocol for a phase II randomised, double-blind, placebo-controlled trial of perampanel as an antiepileptogenic treatment following acute stroke. Issue 5 (10th May 2021) - Nicolo, John-Paul; Chen, Zhibin; Moffat, Bradford; Wright, David K; Sinclair, Benjamin; Glarin, Rebecca; Neal, Andrew; Thijs, Vincent; Seneviratne, Udaya; Yan, Bernard; Cloud, Geoffrey; O'Brien, Terence J; et al.
Abstract : Introduction: Stroke is a common cause of epilepsy that may be mediated via glutamate dysregulation. There is currently no evidence to support the use of antiseizure medications as primary prevention against poststroke epilepsy. Perampanel has a unique antiglutamatergic mechanism of action and may have antiepileptogenic properties. This study aims to evaluate the efficacy and safety of perampanel as an antiepileptogenic treatment in patients at high risk of poststroke epilepsy. Methods and analysis: Up to 328 patients with cortical ischaemic stroke or lobar haemorrhage will be enrolled, and receive their first treatment within 7 days of stroke onset. Patients will be randomised (1:1) to receive perampanel (titrated to 6 mg daily over 4 weeks) or matching placebo, stratified by stroke subtype (ischaemic or haemorrhagic). Treatment will be continued for 12 weeks after titration. 7T MRI will be performed at baseline for quantification of cerebral glutamate by magnetic resonance spectroscopy and glutamate chemical exchange saturation transfer imaging. Blood will be collected for measurement of plasma glutamate levels. Participants will be followed up for 52 weeks after randomisation. The primary study outcome will be the proportion of participants in each group free of late (more than 7 days after stroke onset) poststroke seizures by the end of the 12-month study period, analysed by Fisher's exact test. Secondary outcomes will include time to first seizure, time to treatment withdrawal and 3-month modified Rankin Scale score. Quality of life, cognitive function, mood and adverse events will be assessed by standardised questionnaires. Exploratory outcomes will include correlation between cerebral and plasma glutamate concentration and stroke and seizure outcomes. Ethics and dissemination: This study was approved by the Alfred Health Human Research Ethics Committee (HREC No 44366, Reference 287/18). Trial registration number: ACTRN12618001984280; Pre-results.